Kurdish Students Diaspora in Germany(1945-1975) - Halo, Ali; Mirkhan, Hozan (Humanities Journal of University of Zakho, 2024)
The migration of Kurdish students to Germany between 1945 and 1975 represents a significant phenomenon, marking the emergence of a crucial cultural phase in modern Kurdish history. Following World War II (1939-1945), numerous Kurdish students from affluent and culturally rich backgrounds migrated to Germany for educational purposes. During this period, individuals seeking to enhance their academic and cultural stature were compelled to pursue opportunities in advanced nations like Germany, given the lack of such opportunities in their home countries. Additionally, in the 1950s and 1960s, another wave of Kurdish students migrated to Germany through academic scholarships, while others fled due to challenging political conditions. This research endeavors to address various issues concerning the migration of Kurdish students to Germany from 1945 to 1975. Key inquiries include the motivations behind Kurdish migration to Germany, the quantitative aspect of migration, and the nature of their activities. Through reliance on authentic historical sources, this study aims to provide comprehensive answers to these questions and shed light on this significant aspect of Kurdish migration history.